2013
DOI: 10.11648/j.ajtas.20130206.15
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge, Attitude and Factors Affecting Team Building Amongst Health Workers in Nigeria Using the Permutation Method for Hotelling T-squared Analysis

Abstract: This study is on assessing the knowledge, attitude and factors affecting team building activities amongst health workers in Nigeria. The objective of this study is to determine the equality on knowledge and attitude of team building activities between health workers of Anambra state and Delta State. The source of data for this study was questionnaire, administered randomly to a sample of 200 workers at Anambra State and a sample of 305 workers at the Delta State. The test statistic used was the permutation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In contrast, the study which was conducted by Fleming et al (2011) who found the most common dominant LS in first year was the dual learning category (35%) while a large proportion of the students (53%) in their final year had no dominant LS (39). In contrast, the study was conducted by Erol (2010) in Tukey, who explored the Kolb LSs inventory was used to explore the LS of the study group (40).This is agreed with Aziz et al (2013), who determined Reflector the LS was the most common among the students .The preferred LSs were statistically independent of the demo graphic variables examined such as level of academic years, sex, race and pre-University qualifications (41,42,43). The main reasons might be: the questionnaire used may not be a suitable tool to detect any gender differences in LS or it may not include questions related to the areas of differences.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, the study which was conducted by Fleming et al (2011) who found the most common dominant LS in first year was the dual learning category (35%) while a large proportion of the students (53%) in their final year had no dominant LS (39). In contrast, the study was conducted by Erol (2010) in Tukey, who explored the Kolb LSs inventory was used to explore the LS of the study group (40).This is agreed with Aziz et al (2013), who determined Reflector the LS was the most common among the students .The preferred LSs were statistically independent of the demo graphic variables examined such as level of academic years, sex, race and pre-University qualifications (41,42,43). The main reasons might be: the questionnaire used may not be a suitable tool to detect any gender differences in LS or it may not include questions related to the areas of differences.…”
Section: Discussionmentioning
confidence: 69%
“…It involves the mentor taking personal interest in seeing that a mentee develops talent, skills, expertise and knowledge needed to succeed and have a successful career that contributes to the organization (Barthauer, Spurk & Kauffeld, 2018). Bilesanmi (2013) defined mentoring as a set of tailor-made advice and incentive that a more experienced staff, in an innovative way can offer less experienced members in a plethora way and on a range of competencies.…”
Section: Concept Of Mentoringmentioning
confidence: 99%